Comparison of stress response following microwave ablation and surgical resection of benign thyroid nodules - Liu, Shu-yan; Guo, Wei-hong; Yang, Bo; Li, Yong-feng; Huang, Xiao-yun; Wang, Xiao-qing; Chen, Jie; Xue, Dan; Zhou, Xue-hong (Endocrine, 2019)
Purpose To compare the effects and safety of using microwave ablation (MWA) and surgical resection for the treatment of benign thyroid nodules (BTNs) under ultrasonic guidance and investigate the effects of this treatment on stress response. Methods Patients with BTNs were divided into the MWA and operation groups (72 cases each). Interleukin (IL)-6, IL-8, serum tumor necrosis factor (TNF-α), and hydrostatic visual analog scale (VAS) prior to the operation, at 6 h, 24 h, and 72 h post-operation were compared between the two groups. Operation times, hospitalization times, hospitalization expenses, and postoperative complications in the two groups were also compared. All patients underwent routine ultrasound and thyroid function testing at 3 and 6 months post-operation for assessment of nodule changes and thyroid hormone levels. Results Compared to the MWA group, the operation group had longer average operation times, longer hospital stays, a higher rate of neck pain after surgery, and a higher rate of fever ( P < 0.05). Body temperature, as well as VAS, IL-6, IL-8, and TNF-α levels in the operation group were higher than those in the MWA group at 6 h, 24 h, and 72 h post-operation ( P < 0.05). The levels of free thyroxine and free triiodothyronine in the operation group were lower than those in the MWA group ( P < 0.05). Conclusion MWA is a safe and effective treatment for patients with BTNs. The effects of MWA are more tolerable than those of surgical resection and the physiological function of the thyroid is preserved, which has high clinical value.